Risks of psychosis in methamphetamine users: cross-sectional study in Thailand - Warot Lamyai; Kitkawee Pono; Danai Indrakamhaeng; Apichat Saengsin; Nartya Songhong; Panu Khuwuthyakorn; Pongruk Sribanditmongkol; Anongphan Junkuy; Manit Srisurapanont (BMJ Open)
Objective To determine factors related to recent methamphetamine-associated psychosis (MAP) among individuals recently using methamphetamine (MA).Design Cross-sectional study carried out between July 2015 and June 2017.Setting Four mental health hospitals and one substance abuse treatment centre in Thailand.Participants Individuals recruited onto the study included those aged 18 years or over, of both sexes, who reported MA use in the month prior to admission.Measures Any recent psychosis was confirmed using the Mini International Neuropsychiatric Interview-Plus psychotic module. The Timeline Follow Back was used to determine days of MA use. The severity of MA dependence was assessed using the Severity of Dependence Scale. Quantitative hair analysis was carried out to confirm recent use of MA and to measure the amount of MA use. We compared several characteristics between those who had recently experienced psychosis and those who had not.Results This study included 120 participants without MAP and 113 participants with MAP. The mean age was 28 years and the mean abstinence was 17 days. The levels of MA concentration in hair were not significantly different between groups (p=0.115). Based on the final logistic regression model, the independent factors associated with MAP (OR and 95% CI) included being male (OR 4.03, 95% CI 1.59 to 10.20), ≥16 days of MA use in the past month (OR 2.35, 95% CI 1.22 to 4.52), MA dependence (OR 9.41, 95% CI 2.01 to 44.00) and hospitalisation history related to substance abuse (OR 3.85, 95% CI 2.03 to 7.28).Conclusions Health professionals should closely monitor the development of MAP in MA-dependent men who frequently use MA and have a history of hospitalisation for substance abuse. The measure of MA concentration levels in the hair may add no benefit for the prediction of the development of MAP.